Studi Penggunaan Proporsi Tepung (Sorgum Ketan dengan Beras Ketan) dan Tingkat Kepekatan Santan yang Berbeda Terhadap Kualitas Kue Semprong - Harijono, Harijono; Susanto, W. H.; Ismet, F. (Jurnal Teknologi Pertanian, 2001)
Kue semprong is one of popular traditional snack foods of Indonesia. The research is performed to examine the effect of substitution of waxy rice flour with that of waxy sorghum (Sorgum bicolor Moench) and the solid concentration of coconut milk on the quality attributes of kue semprong. A random1zed block design experiment was performed employing two factors i.e. ratio of waxy sorghum flour (w.s.f.) to the waxy rice flour (w.r.f) and the total solid content of coconut milk. Two levels of ratio (wsf : wrf) were examined 1 : 3 and 1 : 1, and three different total solid contents of coconut milk, namely 23.93%; 17.04% and 11.42% respectively. The experiment was run in triplicates. The results indicated that the best quality kue semprong was obtained by applying ratio of wsf : wrf of 1 : 3 and the coconut milk total solid content of 23.93%. The product contains (% wb) water 1.83, ash 1.18, protein 7.44, fat 7.32 and crude fiber 1.78 respectively. The respective values of breaking force, bulk density and water absorption index were 0.69 kg/cm2; 5.79 ml/g and 12.47 %wb. The sensory evaluation indicated that in terms of the color, appearance, crispiness and taste, the product was well accepted. It was also shown that the product quality was similar to that which was produced using 100% wrf (no substitution). Â  Keywords: kue semprong, traditional snack food, waxy rice flour, waxy sorghum flour